ORGANIZATION OF GREEN PROJECTS FOR THE PURPOSE OF PROMOTION AND SATISFACTION OF USERS IN RURAL REGIONS IN SERBIA - Asmaeil Ali Mohammed Khmaaj; Bojana Ostojić; Biljana Ilić; Milena Cvjetkovic; Jelena Ružić (Ekonomika Poljoprivrede (1979))
The presented study analyzes the impact of green initiatives and new technologies on the tourist experience and user satisfaction in rural areas of western Serbia, focusing on the differences between younger and older populations. Through regression and correlation analysis, it was found that sustainability, green mobility, and the digitalization of services significantly increase the satisfaction of young tourists, while older tourists prefer traditional values such as safety and comfort. The younger population reacts positively to innovations, while the older group seeks stability and practicality. The results suggest that further implementation of sustainable practices and technologies could transform the tourism offering in rural areas, and tailored marketing approaches could effectively address the specific needs of both demographic segments. It is recommended to strengthen the promotion of ecological and technological solutions as the key to future tourism growth in this region.